A preliminary analysis of cloud-based assignments - Aitken, Ashley (IADIS press, 2010)
With the arrival of cloud-based (Web) productivity suites, like Google Docs assignment production and submission may be in for a big change, a change that may help with problems of software availability and managing assignment submission, especially for very large courses. Cloud-based assignment production and submission was introduced into a large first-year common business unit on business information systems and technology. Whilst the students generally welcomed the use of cloud-based productivity tools it was not without its problems. Advantages include the fact the there is no need to purchase or install custom software or transfer files around, the cloud provides access to the service and files anywhere there is an adequate Internet access (and a modern browser), the ability to share rather than submit assignments, and relative ease of plagiarism detection (since the documents are all in electronic format).Disadvantages include possible incompatibilies of Web browsers, the need to introduce new technology to the students, the ease of sharing and thus plagiarism and possibly the limited features in the cloud-based productivity tools. Overall the use of cloud-based assignments was a very satisfactory change for the students, excluding a few glitches here and there, which will no doubt be resolved over time. Staff were also generally very positive about the change, although some lament the increased use of computer screens and miss the legacy approach of marking hard copy assignments. Further work will include a detailed evaluation of the use of cloud-based assignments.